The Interplay between the Otsus Fund, Capital Expenditure, and Regional Economic Performance in Aceh Province - Deni Herdiyana; Resi Ariyasa Qadri; Sutarto; Nur Aisyah Kustiani; Nina Andriana (Jurnal Ilmiah Akuntansi dan Bisnis, 2024)
This study aims to examine the impact of the Special Autonomy Fund on economic growth as measured by Gross Regional Domestic Product (GDRP) in the province of Nanggroe Aceh Darussalam. The research was conducted using the quantitative method of two-stage linear regression analysis. The independent variables used in this research model are General Allocation Funds, Revenue Sharing Funds, Special Allocation Funds, Special Autonomy Funds, and Regional Revenue, while the dependent variable is GDRP. Capital Expenditure is selected as an intervening variable. The data used in this study is panel data from 23 regencies/cities in NAD Province from 2015 to 2020. The research conclusion is that there is an indirect positive effect of the Otsus Fund on GDRP through Capital Expenditures. Therefore, the recommendation for policymakers from the research results is that the Otsus Fund should continue and extend where the Otsus Fund will end in 2028.